Socioleksikografi − eller: ”Det sekundære og afledte er ordbøgerne”. Ny dansk disputats - Farø, Ken; Gottlieb, Henrik (LexicoNordica, 2007)
A new Danish doctoral thesis has been defended at the Aarhus School of Business (2006). Its purpose is to formulate a general lexicographical theory in combination with a specific theory of learners’ dictionaries. Very few theses on this level make such ambitious attempts, making the work a much interesting contribution in the field. We discuss the general contents of the thesis which is mainly theoretically oriented although it maintains a strictly user-oriented perspective. Paradoxically, though, user experiments and surveys play a marginal role here. Instead, the author is more interested in how future dictionaries could be made better which is a laudable goal. Also, the (often harsh) critique formulated is to a large extent well-argued and right. However, we are not quite convinced that the consequent and systematic suggestions deserve the term ’theory’ − at least not if this concept is to be taken in its strict, classical sense. Nevertheless the work of Tarp makes up a very important and inspiring contribution to international metalexicography.